58‐3: Distinguished Paper: High‐Efficient Quantum‐Dot Light‐Emitting Diodes with Blue Cadmium‐free Quantum Dots. Issue 1 (25th September 2020) - Ryowa, Tatsuya; Ishida, Takeshi; Sakakibara, Yusuke; Kitano, Keisuke; Ueda, Masaya; Izumi, Makoto; Ogura, Yuko; Tanaka, Masanori; Nikata, Soichiro; Watanabe, Mayuko; Takasaki, Mikihiro; Itoh, Tetsuji; et al.
Abstract : We report outstanding electroluminescence properties of high efficient blue cadmium‐free quantum dot light emitting diodes (QD‐LED). External quantum efficiency (EQE) of 14.7% was achieved for QD‐LED emitting at 428nm. Furthermore we developed high efficiency and narrow wavelength emission Zinc Selenide (ZnSe) nanocrystals emitting at 445nm and achieved QD‐LED with an EQE of 10.7%. These new QDs have great potential to be used in next generation QD‐LED display with wide colour gamut.